Association Between SIRT1, Cytokines, and Metabolic Syndrome in Schizophrenia Patients With Olanzapine or Clozapine Monotherapy - Fang, Xinyu; Yu, Lingfang; Wang, Dandan; Chen, Yan; Wang, Yewei; Wu, Zenan; Liu, Ruimei; Ren, Juanjuan; Tang, Wei; Zhang, Chen (Frontiers in Psychiatry, 2020)
Objective: Previous studies consistently showed the interaction between Sirtuin1 (SIRT1) and immune inflammation are significant related to metabolic abnormalities, but their role in the pathogenesis of metabolic syndrome caused by second-generation antipsychotics (SGAs) in schizophrenia patients largely remain unknown. Hence, the present study aimed to fill this gap. Methods: A total of 54 schizophrenia patients with olanzapine or clozapine monotherapy (metabolic syndrome, MetS/non-MetS patients, 27/27) and 67 healthy subjects were recruited in the present study. The Positive and Negative Syndrome Scale (PANSS) were used, and the plasma levels of sirtuin1 (SIRT1), interleukin-6 (IL-6), IL-8, IL-10 and Tumor necrosis factor-α (TNF-α) were measured. Results: The results showed that schizophrenia patients treated with olanzapine or clozapine (both MetS and non-MetS groups) had significantly higher plasma levels of IL-6, IL-10 and TNF-α compared to normal controls (All P < 0.05). Moreover, the MetS patients exhibited markedly lower plasma levels of SIRT1 and higher plasma levels of IL-6 than non-MetS patients and normal controls (All P < 0.05). However, there were no significant difference in IL-8 levels between groups. Our correlation analysis showed that SIRT1 was significantly correlated with diastolic blood pressure (DBP), triglyceride (TG) and high density lipoprotein cholesterol (HDL) in schizophrenia patients. The stepwise logistic regression analysis further identified the IL-6 × SIRT1 (beta = -0.463, t = 10.040, P = 0.002) as the influencing factor for the MetS in the patients. Conclusion: Our preliminary findings suggests that SIRT1 interacted with inflammatory cytokines associated with MetS in schizophrenia patients treated with SGAs monotherapy.